2009
DOI: 10.5424/sjar/2009072-423
|View full text |Cite
|
Sign up to set email alerts
|

Sialoglycoconjugate content of milk replacers for neonatal calves

Abstract: Sialoglycoconjugate contents of several milk replacers (MR) currently used in Spain have been determined. The ingestion of these compounds by calves fed bovine milk or MR is also discussed. Total sialic acids and glycoprotein-, oligosaccharide-, casein-, and lipid-bound sialic acids and free sialic acid were determined. High sialic acid contents in all the fractions studied, including total sialic acids, were found. N-acetylneuraminic acid was found to be the major sialic acid in MR. However, MR-D and H had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Glycoconjugates are some of the most important bioactive components in milk, but little or no attention has been paid to these minor components in milk (Martín-Sosa et al, 2009). Previous studies have shown that ST6GAL1, ST8SIA4, and SLC35C1 genes play important roles in the synthesis of glycoconjugates (Hamamoto and Tsuji, 2002;Hellbusch, 2007;Yang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycoconjugates are some of the most important bioactive components in milk, but little or no attention has been paid to these minor components in milk (Martín-Sosa et al, 2009). Previous studies have shown that ST6GAL1, ST8SIA4, and SLC35C1 genes play important roles in the synthesis of glycoconjugates (Hamamoto and Tsuji, 2002;Hellbusch, 2007;Yang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…They protect against pathogens by acting not only as competitive inhibitors through binding on the epithelial surface of the intestine but also as growth promoters for colonic bacterial flora (Newburg, 1999;Gopal and Gill, 2000;Nakano et al, 2001). A number of studies on major components of milk have been performed; however, less attention has been paid to minor components in milk such as glycoconjugates (Martín-Sosa et al, 2009).…”
Section: Introductionmentioning
confidence: 99%